Assessing the Quality of Web Sites - Hasan, Layla; Abuelrub, Emad (INFOCOMP Journal of Computer Science, 2008)
In the age of information technology and with the rapid growth of the World Wide Web, the spectacular growth trend in e-business, that has been experienced so far, is expected to continue. Since the introduction of the first commercial website in 1994, electronic commerce has spread across the globe as a marketing, sales, and communication phenomenon, changing the fact of some business sectors. Companies seeking to achieve significant benefits through e-business need to create an effective and usable web presence to ensure successful interaction and communication with their employees, partners, and customers. Web services are being widely deployed throughout business, education, government, and other organizations. The Internet creates a new business environment, far different from anything that has come before; because it lets a company conducts its entire set of business processes and practices online. As the dependency on web technology increases, the need to assess the factors associated with website success increases as well. This paper reviewed the most recent evaluation criteria methods, which were used in different e-business services. Furthermore, it proposes general criteria for evaluating the quality of any website regardless of the type of service that it offers. The dimensions of the criteria are content quality, design quality, organization quality, and user-friendly quality. These dimensions together with their comprehensive indicators and checklist can be used by web designers and developers to create quality websites to improve the electronic service and then the image of any organization on the Internet.